Assessing the effectiveness of management measures in the Ria Formosa coastal lagoon, Portugal - Newton, Alice; Cañedo-Argüelles, Miguel; March, David; Goela, Priscila; Cristina, Sónia; Zacarias, Marta; Icely, John (Frontiers in Ecology and Evolution, 2022)
The Ria Formosa is an important transitional and coastal lagoon on the south coast of Portugal that provides valuable ecosystem services. There is a great potential for Blue Growth sectors, such as aquaculture and coastal tourism, but these rely on good water quality. This work addresses the effectiveness of management measures, such as wastewater treatment plant implementation and dredging, on the water quality of the Ria Formosa coastal lagoon system. The ecological status of Ria Formosa was evaluated, according to the physico-chemical and biological quality elements, of the Water Framework Directive (WFD). The main indicators were the physico-chemical quality elements of nutrient and oxygen condition and the biological quality element of chlorophyll a as a proxy for phytoplankton biomass. The data were analysed to check whether they were consistent with the WFD water body classification. The data after the management measures was compared with historical data in order to evaluate if these measures had been effective. The relation between nutrient pressures and meteorological conditions, especially rainfall and runoff was also addressed. Results showed a decrease in nutrient concentration after the management interventions, despite the increase of population and intensifying agriculture in the catchment. The Ecological Status is spatially variable with an overall moderate status, indicating the need for further management measures. There is a significant reduction in nutrient pressure on the lagoon during drought years. This indicates that climate change may alter the structure and function of the lagoon.